Government marketing: a public administration’s concept (Revista de Investigaciones Universidad del Quindío, 2022)
The concept of government marketing is developed as part of an expansion of concepts in public administration. In Anglo-Saxon literature, there are some approximations while for the Hispanic world it is still an anecdotal issue. Postmodern culture has privileged popularity and image as transmitters of ideas. Government communication has always existed, but from this new reality, it becomes essential to have a strategic mechanism that channels communication in the best way to generate better relations between the government and the citizen, where government marketing appears.
Keywords: Government marketing; public administration; image; brand